Analisis Cost of Illness Pada Pasien Hipertensi Peserta BPJS Rawat Jalan di Puskesmas Banyuanyar - Etika, Trias (Pharmaceutical Journal of Indonesia, 2020)
Hypertension is a chronic disease that requires regular therapy to control blood pressure. The cost of treating hypertension can be measured using a Cost of Illness analysis. The Purpose of this study to find out the total cost of treating hypertensive patients participating in BPJS with Captopril therapy for one year for outpatient treatment at the Banyuanyar Public Health Center in Sampang Regency. Method this study used a non-random sampling technique with a purposive sampling method. This research conducted at Banyuanyar Health Center with total sample 40 people. The instrument used a structured interview which was previously tested for validity. Data were analyzed using Microsoft Excel. Result and Conclusions this study is the cost of illness for hypertensive patients for one year is Rp. 36,140 to Rp. 2,528.000. The total range of direct medical costs is Rp. 36,140 to Rp. 368.000 per patient, the range of direct non-medical costs is Rp. 0 to Rp. 360,000 per patient, and the range of indirect costs is Rp. 0 to Rp. 1,800,000 per patient. The large cost value range and small cost value are influenced by the frequency of patient visits.Â  Small costs are cheaper but with the frequency of patient visits and disorderly patient compliance so that the therapeutic effects achieved are less good, while large costs are more expensive but with the frequency of patient visits and orderly patient compliance so that the therapeutic effects achieved are good and maximal.